Loss of Seed-Dispersing Animals and Its Impacts on Humanity - Santos, Gilney Charll; Chaves, Leonardo Silva; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2017)
Seed dispersal is a key ecological process for the maintenance of biodiversity and ecosystem functioning and is undoubtedly critical to the provision of valuable ecosystem benefits to humanity. However, the loss or population reduction of seed-dispersing animals, especially the medium and large ones, has increasingly compromised important ecological processes and associated ecosystem benefits. Thus, we aimed to review researches that examined how the loss or reduction of seed-dispersing fauna affects the functioning of ecosystems and, consequently, humanity. We believe that this review provides new directions for future research in the field of conservation science that may contribute to policy initiatives and management and conservation plans.